Presurgical evaluation of malignant neck nodes by assessment it’s Intranodal vascularity using the color Doppler ultra sound (Mustansiria Dental Journal, 2018)
Color Doppler ultra sound is an ideal imaging tool for initial assessment ofintranodular vascularity which may reflect some pathological behaviors of tumorsand lymph nodes in patients with cervical lymphadenopathy. The aim of this studywas to evaluate the usefulness of Color Doppler ultra sound in differentiatingbenign from malignant cervical lymph nodes by the assessment of Nodalvascularity. In a prospective study of 24 untreated patient with 65 cervical lymphnodes clinically including enlarged hard and soft palpable and non palpable lymphnodes . All these lymph nodes were evaluated with Color Doppler ultra sound as apre-surgical diagnostic tool, the findings were compared with histo-pathalogicalresults.Fine needle Aspiration cytology was used for 15 palpable enlarged cervicallymph nodes, most of these lymph nodes 12 lymph nodes were associated withreactive lymph nodes and not operated on, just follow up with antibiotic treatmentand performed only 3 lymph nodes were associated with malignant lymph nodeswhich removed surgically and assessed histopathologically.Upon Color Doppler ultra sound examination pre-operatively of 65 cervicallymph nodes were found 20 lymph nodes as a reactive lymph nodes and 45 asmalignant lymph nodes.After neck dissection, all lymph nodes histo-pathologically examined whichshowed 22 benign lymph nodes and 43 lymph nodes containing metastases. Nodalvasculature were classified into:· Hilar· Capsular· Hilar with capsular vascularityResults: most of the malignant nodes showed the presence of capsular vascularity andcapsular with hilar vascularity, 37.2% and 48.8% respectively, where as themajority of the reactive nodes showed hilar vascularity 77.3% and the different washighly significant P